Estética e imagem corporal de mulheres jovens - Silva, Greicielle Pereira Arruda e (2015)
The aesthetic and physical appearance influence individual and collective behavior and increasingly has been studied. The physical size is a common attribute of beauty, health, sexual and reproductive signs in women. The aesthetic and body image is important for physical and mental health component and is one of the objects of work areas involving physical exercise and nutrition. OBJECTIVE: To propose a formula to estimate body aesthetic note of young women and to investigate the difference in aesthetic judgment for men and women, and the association between body image and anthropometric variables in young women athletes and non-exercising. METHODS: The sample consisted of 65 women 25.2 ± 4.3 years. For the assessment of body image use the Body Shape Questionnaire (BSQ) and the scale of Stunkard silhouettes. Anthropometric measurements were made and photographs of previous view, profile and later wearing a patterned bikini. How the practice of physical activities and exercises used the international physical activity questionnaire (IPAQ). The aesthetic note was given by a jury of 33 physical education teachers, 19 men and 13 women, with their average age (27.79 ± 5.78; 29.85 ± 2.97). For association was used Pearson correlation coefficients and the comparison between variables was by paired t test. The estimate of aesthetic note of the equation was the multiple linear regression with significance p = 0.05. RESULTS: Both groups showed similarities in BMI and all studied circles. As for the BSQ, we observed that in the exercise practitioner group 59% had image disturbance by BSQ, and 75% group not practicing physical exercise. In assessing the self-image by the silhouette of scale, both groups showed a desire to decrease physique. We observed that both instruments showed significant correlations with anthropometric variables in the two study groups. The average values of the note voted for men and women did not differ when compared, and the overall average. Only variables: fat weight (kg), IAQ and CMC influenced the aesthetic evaluation. The correlation values of these variables with voted aesthetic note were significant (r = -0.651 Weight Gkg p = <0.001; IAQ = -0.505, p = <0.001; CMC = 0.336 and p = 0.006). Mean comparisons of voted aesthetic notes and notes aesthetic estimated by the equation and which were not different (p = 0.50). The aesthetic rated notes and notes estimated aesthetic were significantly correlated (r = 0.81; p <0.0001). CONCLUSION: Women young independent of BMI and physique expressed concern and dissatisfaction with body image. The physical exercise promotes a better self-assessment of body image. The negative association between body fat and IAQ and aesthetic suggests that the main component to be modified to improve aesthetics is body fat, and the IAQ when excessive, and even muscle development thigh demonstrated importance in aesthetic evaluation. You can estimate the aesthetic evaluation in young women with anthropometric measurements.